Patronage as the politics of South Asia - Piliavsky, Anastasia, 1981- (Cambridge University Press, 2014)
"Focuses on the persistent norms of conduct and communication, forms of economic and ritual exchange, and mutual expectations, which distinguish patronage patterns in South Asian countries from those observed anywhere else"--